Normative Analysis of Election Law in Timor-Leste - Cruz, Carolina da (CV. ULIL ALBAB CORP, 2026)
Discussing issues surrounding general elections and political party organization means we are talking about the involvement of citizens ara. In the context of a democratic country, one tangible form of citizen involvement is through participation in the general election process. The desires and hopes of the people are generally represented by a political party entity. In countries that practice democratic principles, the idea related to citizen participation is that citizens have the right to participate in determining leaders who will influence public policy. This study uses a normative method to analyze the legal materials used. The type of research used is normative juridical, which is a type of research conducted by studying existing norms or laws and regulations related to the issues discussed. The data sources obtained include official documents, books, and applicable laws and regulations. Based on the results of this study, East Timor's electoral law has normatively met international and modern standards, serving as a key pillar in building strong democratic institutions. However, continuous improvement in constitutional and implementation aspects is still needed to overcome political complexity and ensure the effectiveness of governance. The general legal framework for elections in Timor-Leste is in line with the basic principles of democracy and universal human rights. The country's constitution and election laws guarantee fundamental rights, although there are challenges in implementation and regulatory coherence.